1985
DOI: 10.1002/app.1985.070300722
|View full text |Cite
|
Sign up to set email alerts
|

Curing of epoxy resins with diphenyliodonium salts as thermal initiators

Abstract: SynopsisThe curing reaction of a thermally curable epoxy system containing diphenyliodonium hexafluoroarsenate was investigated by using the dynamic and isothermal techniques of differential scanning calorimetry (DSC). It was shown that the curing involved two consecutive reactions. The heat of the total curing reaction and overall kinetic parameters for the two reactions were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 9 publications
3
37
0
Order By: Relevance
“…In general, the polymerization reaction of cationic epoxy system leads to a Lewis acid process. 13 Gu et al 5 who had studied on diphenyliodonium hexafluoroarsenate/ epoxy system suggested that the two different curing reactions occur. Based on Gu's suggestion and DSC results, it may be considered that two separate initiation reactions behave as follows; …”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the polymerization reaction of cationic epoxy system leads to a Lewis acid process. 13 Gu et al 5 who had studied on diphenyliodonium hexafluoroarsenate/ epoxy system suggested that the two different curing reactions occur. Based on Gu's suggestion and DSC results, it may be considered that two separate initiation reactions behave as follows; …”
Section: Measurementsmentioning
confidence: 99%
“…And it has been proved by Pappers et al 3 and Endo et al 4 that several sulfonium salts act as thermally latent cationic initiator in the curing reaction of epoxy resins, cyclic ethers, and vinyl monomers. Gu et al 5 and Morio et al 6 also reported that the aliphatic sulfonium salts can be also excellent thermally latent initiators for epoxy resins without any co-initiator. Generally, the network formation leading to the crosslinking in polymers is known as a complex process and it is of a specific interest in both basic and applied studies.…”
mentioning
confidence: 99%
“…The epoxy value of ECO was tested by the following procedure [27] : ECO (about 0.5 g) was weighed into a flask and 20 mL of hydrochloric acid-acetone solution added and swirled until the ECO sample was dissolved. Then, the solution was allowed to stand in the dark for 30 min and titrated with 0.1 mol$L -1 aqueous NaOH solution, using methanolic methyl red as an indicator.…”
Section: Epoxy Valuementioning
confidence: 99%
“…These complexes overcome the disadvantage of excessively rapid gelation, human toxicity, high hygroscopicity, and light instability [4]. Particularly, development of latent catalysts for cationic polymerization is desirable for enhancement of both the pot-life and handling of thermosetting resins [5,6]. Among them, N-benzylpyrazinium salt has been shown to be an excellent latent thermal initiator for epoxy matrix resins [7,8].…”
Section: Introductionmentioning
confidence: 99%